Effect of body size on operative risk of carotid endarterectomy. Issue 12 (16th November 2004) - Messé, S R; Kasner, S E; Mehta, Z; Warlow, C P; Rothwell, P M
Abstract : Many studies have found that women have a higher risk of perioperative stroke or death from carotid endarterectomy. Other vascular surgical procedures have demonstrated that body size and morphology impact on operative risk. We correlated the 30 day operative risk of stroke and death in the European Carotid Surgery Trial (ECST) with height, weight, body surface area (BSA), and body mass index using single variable analyses and multivariable logistic regression. Women were at significantly higher risk of perioperative stroke and death in the ECST. Both height and BSA confounded the effect of sex, implying that the generally smaller size of women may contribute to their increased risk. This finding should be validated in other large datasets.